Geographic Information System Mapping of Plantation - Pramuditha Shinta Dewi Puspitasari; Agus Kurniasari, Arvita; Trismayanti Dwi Puspitasari (Journal of Applied Science, Engineering, Technology, and Education, 2022)
Perusahaan Daerah Perkebunan (PDP) Kahyangan is a Regional Owned Enterprise in Jember Regency which was formed to realize the prosperity of the community. In Regional Regulation Number 2 of 2012-chapter 3 clauses 2, the government can manage regional finances by exploring sources of Regional Original Income, one of which is from the PDP. In addition, the purpose of the establishment of the PDP is as a means of developing the economy in the context of regional development by increasing productivity from all aspects to increase regional income. The main commodities are coffee and rubber, cloves, Mahoni, and Sengon wood are supporting commodities. Based on interviews PDP's profit contribution to Jember's income has continued to decline in recent years due to the absence of good management of its potential. So, this research will manage a system that can assist in obtaining information about the distribution of plantation land commodities in Jember, as well as mapping existing commodities by Geographic Information System (GIS). The method for developing GIS uses a Design Sprint. The output of this method prototypes and will implement in the GIS application.